Influence of the application of ultrasound during the synthesis of calcium phosphates - Pelizaro, Thales A. Garcia [UNESP]; Tolaba, Angel G.; Rodriguez-Chanfrau, Jorge E. [UNESP]; Veranes-Pantoja, Yaymaliris; Guastaldi, Antonio C. [UNESP] (American Scientific Publishers, 2018)
The ultrasonic assisted synthesis of apatite is an ideal technique to be used in the production of nanostructured compounds. Nowdays in medicine, porous apatite nanostructure materials are widely used in bone regeneration processes. Sonication is a process where an acoustic field applied to a liquid medium is used. Ultrasonic waves propagate in the liquid causing a process known as cavitation. This process generates an extreme force that results in collisions between particles causing a decrease in their size. This reduction in size may generally produces particles in the order of microns and nanos. Recent studies have demonstrated that the application of ultrasound in the wet chemical synthesis of different phases of calcium phosphate reduces the particle size of the material obtained. The objective of this work was to evaluate the influence of ultrasound during the process of synthesis of different apatite phases. Three phases of apatite were synthesized according to the described methodology in literature. During the synthesis process, ultrasound was used. The material obtained was characterized by X-ray Powder Diffraction, FTIR spectroscopy and Scanning Electron Microscopy. The particle size was determined by scanning electron microscopy. The results showed that the particle size decreases with the application of ultrasound in the established working conditions.
Keywords: Apatite; Nanostructured; Particle Size; Synthesis; Ultrasound